Buprenorphine Prevalence in DUID Cases in Southwestern Virginia: Case Studies and Observations. Issue 1 (12th November 2020) - Kuhlman, James J; Harris, Chad; Wright, Trista
Abstract: Buprenorphine, a semisynthetic mixed agonist/antagonist opioid used primarily for the treatment of opioid use disorder, was reported in 194 driving under the influence of drugs (DUID) cases in Southwestern Virginia during the period from 2017 through 2019. Identifying and confirming buprenorphine in DUID cases is common in this region. Interpretation is complex due to the large range of concentrations of buprenorphine found in blood and frequent combinations with other therapeutic and abused drugs. Buprenorphine was identified by immunoassay and quantified by liquid chromatography–tandem mass spectrometry. A sensitive method was necessary as one-third of concentrations of buprenorphine and/or norbuprenorphine were <1.0 µg/L. Concentrations of buprenorphine ranged from <0.5 to 11 µg/L (mean 2.5 µg/L, median 1.8 µg/L) and concentrations of norbuprenorphine ranged from <0.5 to >20 µg/L (mean 3.3 µg/L, median 2.2 µg/L). Buprenorphine polysubstance use was common. Only 10% of the cases examined did not contain other drugs confirmed in routine DUID screening tests. The most common drug groups confirmed were benzodiazepines, amphetamines and cannabinoids. The DUID case histories presented represent examples of buprenorphine abuse, buprenorphine with no other drug groups, buprenorphine combined with other drug groups, cases consistent with impairment and cases with minimal impairment. Central nervous system depressant and narcotic analgesic symptoms were commonly observed; however, some cases contained stimulant symptoms. Buprenorphine-to-norbuprenorphine (B/NB) ratios had a mean and median ratio of 1.1 and 0.8, respectively. B/NB ratios >3.0 were found in 4.7% of the cases. The finding of a higher B/NB ratio may indicate a more recent buprenorphine administration and a greater potential for impairment. No relationship between the concentration of buprenorphine and/or norbuprenorphine in blood and the performance on drug recognition expert evaluation or standardized field sobriety tests could be determined.